Computational issues in the simulation of high speed ballistic impact: a review - Mohd Norihan, Ibrahim; Adi Siswanto, Waluyo; Zaidi, A. M. A. (Trans Tech Publication Ltd, 2013)
This paper presents a review of recent developments of nonlinear constitutive material models for the applications in high speed ballistic impact of projectile into several types of targets. The objective is to comprehend some numerical approaches that have been proposed and used in the technical literatures especially regarding bullet-target interaction. Attention is given on the application of several types of computational constitutive models and simulations used to represent the projectile characteristic, ballistic penetration, failure modes in target and deformation pattern. This paper serves as a concise source to identify future direction in the area of computational mechanics of high speed collisions and provides brief literatures for those interested in conducting research into the topic